Persepsi Masyarakat terhadap Limbah Tempat Pemotongan Hewan (TPH) Kuda di Kabupaten Jeneponto Sulawesi Selatan - A. Lestari; H. Nuraini; R. Priyanto; Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Jeneponto was known as a regency with highest population of horses because of horse meat wascommon food in Jeneponto. High consumption of horse meat affected the number of horse slaughterhouses,however the slaughterhouses was owned by residents and was managed traditionally. Poor management,location that close from residency, and waste that was produced from the slaughterhouses led todisturbance against the community that lived close to the horse slaughterhouses. Questionnaires wereused in survey to collect data about community perceptions towards slaughterhouses waste. There were182 respondent in this research that was selected through purposive sampling. The result of surveyrevealed that 48.90 % respondent was disturbed by bad odor, 22.53 % was disturbed by noise, and 23.63% was disturbed by insect and pest from the horse slaughterhouses. Majority of respondent (51.65 %)contended that slaughterhouses waste management was fully the responsibility of slaughterhouse owner,however only 12.09 % of respondent that ever protested the slaughterhouse that they were experienced